If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 20 = 12x + 84 Reorder the terms: 20 + 4x = 12x + 84 Reorder the terms: 20 + 4x = 84 + 12x Solving 20 + 4x = 84 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 20 + 4x + -12x = 84 + 12x + -12x Combine like terms: 4x + -12x = -8x 20 + -8x = 84 + 12x + -12x Combine like terms: 12x + -12x = 0 20 + -8x = 84 + 0 20 + -8x = 84 Add '-20' to each side of the equation. 20 + -20 + -8x = 84 + -20 Combine like terms: 20 + -20 = 0 0 + -8x = 84 + -20 -8x = 84 + -20 Combine like terms: 84 + -20 = 64 -8x = 64 Divide each side by '-8'. x = -8 Simplifying x = -8
| -2(4b+1)+(9b-6)=0 | | 8p-6-3p+2=15+2p+2 | | (-2x^3+4)(2x^2+5)= | | 13-10x=43-24x | | 3y-12=2(2y+44) | | (3x-3)(x-9)= | | 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 |